PEDAGOGICAL VIEWS OF UKRAINIAN AVANT-GARDE ARTISTS AS THE METHODOLOGICAL BASIS OF MODERN NATIONAL ART PEDAGOGICS - KUCHER, Svitlana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article examines the problem of forming the methodological basis of modern Ukrainian art pedagogy, the conceptual basis of which should be the work of Ukrainian avant-garde at the beginning of the 20th century, since it was during that period that art education found its national expression. As in the period of the avant-garde, the domestic pedagogy of art is currently in the process of formation and must find ways to raise the authority of the specifically Ukrainian in art, not formal, but essential. Studying the activities of artists of Ukrainian avant-garde and other stylistic currents of the first half of the 20th century, their "re-Ukrainization" and understanding of artistic and pedagogical theory and practice should form the basis for restructuring approaches in art pedagogy. Based on the analysis of art history, history and pedagogical literature, the leading ideas of Ukrainian artists-pedagogues were identified, who consciously relied on Ukrainian cultural traditions in their activities, and, at the same time, promoted the ideas of art development in harmony with world cultural progress. In view of the task of art education, the principles of art pedagogy were specified based on the short-lived but valuable experience of Ukrainian independence in this field at the beginning of the 20th century. Ukrainian modernist and avant-garde art, being an important part of the world cultural process, gave impetus to the development of modern currents and concepts, contributed to the liberation and appreciation of the personal nature of creativity, made it possible to turn to folk roots as a source of inspiration. The principles of art pedagogy are formulated taking into account the achievements of the actors of art education institutions of the beginning of the 20th century: a combination of general artistic (technical) training with the freedom to choose the direction of creative development for both the teacher and the student; multi-instrumentalism of the future teacher-artist; style pluralism in education; search and research in the educational process based on the best achievements of national and world culture.